Spatial and temporal differences in Acropora cervicornis colony size and health - Goergen, Elizabeth A; Lunz, Kathleen Semon; Gilliam, David S (Advances in marine biology, 2020)
Little to no recovery in Acropora cervicornis populations has been documented since the 1970s and 1980s widespread disease events, and disease and predation appear to remain significant drivers of mortality. However, to date, demographic studies of A. cervicornis lack data temporally or spatially sufficient to quantify factors limiting recovery. Acropora cervicornis populations in three regions [Broward County (BWD), Middle Keys (MDK), and Dry Tortugas (DRTO)] of the Florida Reef Tract were surveyed up to three times per year from 2011 to 2015. Temporal and spatial differences were evaluated for colony size, live tissue volume, and prevalence and impact of disease and predation. Significantly larger colonies were reported in BWD, and at relatively deeper or more sheltered sites. At least 43% of colonies in each region were of reproductively capable size. Mean relative change in colony size between surveys (3-5 months) ranged from -20% to 19%. Disease and predation were consistently present in all regions, but levels varied significantly across space and time. Disease prevalence was the most variable condition (ranging from 0% to 28% per survey), increasing after periods of elevated temperatures and environmental disturbances, and caused significantly more partial mortality than fireworm (Hermodice carunculata) or snail (Coralliophila spp.) predation. Recovery potential and long-term persistence of this species may be limited due to the persistent presence of disease and predation, and reproductive limitations. However, there is still potential at sites of greater depth and/or more protection hosted larger and healthier colonies creating potential refugia for this species.